CONTROVERSIAL ISSUES REGARDING THE USE OF GADOLINUM-BASED CONTRAST AGENTS – THE LATEST REPORTS - Małgorzata Piekarska-Kasperska; Julia Błoniecka; Jan Kamiński; Anna Daniel; Natalia Kraciuk; Radosław Kasperski; Kacper Jankowski; Alicja Bury; Karol Bartecki (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Gadolinium-based contrast agents (GBCAs) are paramagnetic substances that have been used over the past 30 years in MRI diagnostics, and have significantly improved imaging and diagnostic capabilities for many diseases. Although they are used in small amounts in individual patients, their use worldwide involves the consumption of many thousands of liters of GBCAs per year and is growing. With such widespread demand for contrast-enhanced MRI, there is a need for these agents to be as safe as possible.Review methods: A comprehensive literature review was conducted, analyzing 33 studies from the PubMed and Google Scholar database (English-language, published within the last 8 years).Brief description of the state of knowledge: In recent years, much attention has been paid to the fact of gadolinium deposition in tissues and accumulation in the environment, the risk of nephrogenic systemic fibrosis (NSF), and safety issues in use in pregnant patients and the pediatric population. The risk of the above-mentioned events has been shown to vary depending on the type of GBCA, with macrocyclic GBCAs having a lower risk than linear GBCAs. Despite a great number of studies, many issues regarding the clinical significance of the side effects of GBCAs still remain unclear and controversial. Therefore, even more stable and better-performing GBCAs, new MRI approaches requiring lower doses of GBCAs, and alternative contrast agents need to be developed to ensure patient welfare.Summary: In this review, we will try to present the current state of knowledge on the above-mentioned issues with a perspective of the future of this branch of medicine.